Socialization of Marketing Strategies for Chicken Livestock Products in Cicenang Village, Cigasong District, Majalengka Regency. - Imma Ismaniar; Muhammad Fikry Januar; Dede Ibrahim Maulana; Solihin; Eko Prasetyo (Politeknik Mardira Indonesia, 2026)
This Community Service Program (PKM) aims to overcome the barriers of conventional marketing and the low digital literacy among chicken livestock farmers in Cicenang Village, Majalengka. Although the village possesses significant livestock business potential, its market reach remains highly restricted. The primary target of the PKM consisted of local farmers who possessed limited technological proficiency. Therefore, the proposed solution centered on an extremely simple and applicable digital education approach (zero-digital-knowledge), encompassing soft-selling concepts and the optimization of familiar tools. The methodology utilized a Participatory and Hands-on Practice approach, featuring simplified lectures, practical training on using WhatsApp Business for product catalog creation, and crucial technical assistance, including the registration and verification of the livestock business locations on Google Maps. The main outputs targeted were an increase in basic marketing literacy and the establishment of digital assets for the businesses. The results demonstrated an average increase in participant understanding scores of 45% regarding branding and soft-selling concepts. Implementationally, 100% of core livestock farmer groups were successfully registered and verified on Google Maps, instantly enhancing the geographic visibility of their businesses. Furthermore, 75% of participants showed fundamental skills in creating product catalogs using WhatsApp Business. Overall, PKM successfully delivered permanent digital assets and crucial minimal practical skills necessary to enhance the competitiveness and foster the economic independence of the farmers in the digital era.